2018
DOI: 10.1530/jme-16-0257
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin protects against cytokine-induced beta-cell death by NFκB and JNK inhibition

Abstract: Type 1 diabetes is caused by an autoimmune assault that induces progressive beta-cell dysfunction and dead. Pro-inflammatory cytokines, such as interleukin 1 beta (IL1B), tumor necrosis factor (TNF) and interferon gamma (IFNG) contribute for beta-cell death, which involves the activation of the nuclear factor kappa B (NFκB) and c- Jun N-terminal kinase (JNK). Prolactin (PRL), a physiological mediator for beta-cell proliferation, was shown to protect beta cells against cytokines pro-apoptotic effects. We presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 50 publications
1
10
0
1
Order By: Relevance
“…In the present study, we demonstrated that the JNK pathway was profoundly activated in β cells by proinflammatory cytokines and oxidative stress. This does not contradict the findings that demonstrated the role of both NF- κ B and JNK signaling in rat β cell death that is induced by proinflammatory cytokines [ 42 ]. Interestingly, PRDX6 downregulated the JNK activity in β cells exposed to TNF- α and IL-1 β , suggesting that oxidative stress and subsequent activation of the JNK pathway could be involved in the pathogenesis of T1D.…”
Section: Discussionsupporting
confidence: 72%
“…In the present study, we demonstrated that the JNK pathway was profoundly activated in β cells by proinflammatory cytokines and oxidative stress. This does not contradict the findings that demonstrated the role of both NF- κ B and JNK signaling in rat β cell death that is induced by proinflammatory cytokines [ 42 ]. Interestingly, PRDX6 downregulated the JNK activity in β cells exposed to TNF- α and IL-1 β , suggesting that oxidative stress and subsequent activation of the JNK pathway could be involved in the pathogenesis of T1D.…”
Section: Discussionsupporting
confidence: 72%
“…Additionally, CAV1 overexpression induced the activation of ERK, JNK and p38 signaling pathways in Hepa1-6 cells [ 57 ]. MAPKs have been associated with both anti- [ 58 , 59 , 60 ] and pro-apoptotic [ 18 , 19 , 20 , 21 , 22 , 23 , 61 ] effects in beta cells. Currently, the prevalent notion is that JNK and p38 activation induced by FFAs in beta cells is pro-apoptotic, while ERK1/2 activation is considered more anti-apoptotic [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whether these responses protect against cell demise or, conversely, promote stress-induced cell death, appears to be cell context-dependent [ 17 ]. Activation of these MAPK pathways in response to cellular stress has been implicated in apoptotic-signaling responsible for beta cell loss [ 18 , 19 , 20 , 21 , 22 , 23 ]. CAV1 has been linked to the regulation of MAPKs by either activating or inhibiting these kinases, with different consequences concerning cell viability.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Yamamoto et al suggest that rhPRL has a cytoprotective effect on the islets of Langerhans, which may improve the survival of pancreatic grafts [29]. It may result from the participation of PRL in the anti-apoptotic mechanism and reduction of pro-apoptotic effectors, and consequently, protect cells against inflammation [30].…”
Section: Discussionmentioning
confidence: 99%